Cognitive Stimulation in Children with Severe Speech Impairment (Early Childhood Education & Parenting (ECEPA), 2025)
This article discusses speech disorders that may occur in children, particularly those resulting from disruptions in cognitive processes. Such disorders are especially prevalent among children with special needs who experience severe speech impairments. The aim of this article is to provide information on various types of speech disorders, which are often associated with organic damage to the central nervous system, and to offer guidance on appropriate stimulation strategies to support affected children. The research method employed is a literature review. The findings outline stages and exercises that can be implemented to assist children with speech disorders. The article also emphasizes the importance of collaboration between educators and speech therapists in diagnosing and addressing these challenges.
Keywords: Speech delay; Dysarthric children; Cognitive process